Enterprise wireless local area network architectures and technologies - Wu, Rihai (Boca Raton, FL : CRC Press, 2021)
"This book has been written with the support of Huawei's large accumulation of technical knowledge and experience in the WLAN field, as well as its understanding of customer service requirements. The book first covers service challenges facing enterprise wireless networks, along with detailing the latest evolution of Wi-Fi standards, air interface performance, and methods for improving user experience in enterprise scenarios. Furthermore, it illustrates typical networking, planning, and scenario-specific design for enterprise WLANs, and provides readers with a comprehensive understanding of enterprise WLAN planning, design, and technical implementation, as well as suggestions for deployment. This is a practical and easy-to-understand guide to WLAN design, and is written for WLAN technical support and planning engineers, network administrators, and enthusiasts of network technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Wireless LANs; COMPUTERS / Networking / General; TECHNOLOGY / Telecommunications